2023
DOI: 10.1021/acsmedchemlett.3c00093
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Peptides Incorporating Halogenated Marine-Derived Amino Acid Substituents

Abstract: Small synthetic mimics of cationic antimicrobial peptides represent a promising class of compounds with leads in clinical development for the treatment of persistent microbial infections. The activity and selectivity of these compounds rely on a balance between hydrophobic and cationic components, and here, we explore the activity of 19 linear cationic tripeptides against five different pathogenic bacteria and fungi, including clinical isolates. The compounds incorporated modified hydrophobic amino acids inspi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…79 Similar building blocks are generally used in synthetic halogenated AMPs, leading to an increase of the hydrophobic volume of Phe and Trp residues. 73 Molchanova et al demonstrated that inactive peptoids can be converted into effective antibacterials by bromination of Phe residues without leading to increased haemolytic activity or in vitro cytotoxicity. 74 Similarly, a study by Jia et al evidenced the improved proteolytic stability of several halogenated derivatives of the honeybee peptide Jelleine-1 (PFKLSLHL-NH 2 ), with the iodinated analogue displaying an eightfold increase in the antimicrobial activity with respect to the parent peptide.…”
Section: Interaction With Bacterial Membranes – Design Rulesmentioning
confidence: 99%
“…79 Similar building blocks are generally used in synthetic halogenated AMPs, leading to an increase of the hydrophobic volume of Phe and Trp residues. 73 Molchanova et al demonstrated that inactive peptoids can be converted into effective antibacterials by bromination of Phe residues without leading to increased haemolytic activity or in vitro cytotoxicity. 74 Similarly, a study by Jia et al evidenced the improved proteolytic stability of several halogenated derivatives of the honeybee peptide Jelleine-1 (PFKLSLHL-NH 2 ), with the iodinated analogue displaying an eightfold increase in the antimicrobial activity with respect to the parent peptide.…”
Section: Interaction With Bacterial Membranes – Design Rulesmentioning
confidence: 99%
“…Compounds produced by vertebrate innate immune systems have been studied and optimized to generate truncated mimics with potential medical and antifouling applications . Small synthetic mimics of antimicrobial peptides, decorated with unnatural cationic and hydrophobic amino acids, have been shown to maintain the activity of the native defense protein counterparts. We have explored a selection of linear tripeptides in an aqueous environment to assess their potential effect on the different stages of the biofouling process . Perhaps unexpectedly, we demonstrated that short peptidomimetics are highly efficient against the growth and adhesion of marine bacteria and barnacles.…”
Section: Structure–activity Relationshipsmentioning
confidence: 99%